Development of an evaluation model of environmental parameters to achieve thermal comfort in homes in Kallapuma - Girón Pizarro, María Lourdes (2024)
The present research is based on the study of the thermal comfort of the residents of the Minor Population Center of Kallapuma located at 4258 meters above sea level in the district of Tarata, province and region of Tacna. To evaluate the environmental parameters, satisfaction surveys were applied taking into account clothing, nutrition, physical activity and thermal comfort. Likewise, a device called TSVR was used that allowed measuring temperature, relative humidity, perceptions of comfort such as thermal sensation, personal information and clothing worn by the user, called thermal sensation vote (VST). These measurements were taken in the months of May, June and July of 2022. The real acceptability of thermal conditions to users was analyzed. Once the data was obtained, the neutrality temperature and thermal comfort ranges for the population of the Minor Population Center of Kallapuma were identified, taking into account the ASHRAE 55 and ISO 7730 standards and comparing them with models developed by authors such as Fanger, Humphreys, Givoni, among others. Knowing the defined conditions of thermal comfort and the type of population will favor the design of homes in high Andean areas. Expressing the conditions related to temperature, relative humidity and perceptions of thermal comfort facilitates the application of passive environmental conditioning strategies.